Rebleeding of a Splenic Artery Aneurysm after Coil Embolisation - Kyra D. Kingma; Antonius N. van der Linden; Rudi M. H. Roumen (Case Reports in Surgery)
Background. Splenic artery aneurysm (SAA) is an uncommon and difficult diagnosis. SAA is more common in females. Only 20% of SAA is symptomatic and may present as a rupture. A ruptured SAA is associated with a 25% mortality rate. Case Presentation. We present a case of a male patient with a bleeding SAA that rapidly increased in size. Distal coiling was technically impossible and despite proximal coil embolisation the SAA continued to bleed. A laparotomy including splenectomy and partial pancreatectomy was performed with an uneventful patient recovery. Discussion. Endovascular management is currently considered the optimal treatment of SAA. However, careful monitoring and follow-up is needed after embolisation as rapid recanalization of the SAA may possibly occur, especially when distal coiling of the aneurysm is unsuccessful. Conclusion. Endovascular treatment of an SAA is not necessarily effective. Surgeons must be prepared to perform open procedures to further reduce mortality rates.